2012
DOI: 10.3390/cryst2031058
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and Molecular Structures of Two 2-Aminothiophene Derivatives

Abstract: Abstract:The crystal and molecular structures of two 2-aminothiophene derivatives, potential allosteric enhancers at the human A 1 adenosine receptor, are reported. (2-Amino-4,5,6,7-tetrahydro-1-benzothiophen-3-yl)(phenyl)methanone (1) crystallizes in the orthorhombic space group Pna2 1 (a = 9.2080(4) Å, b = 14.0485(7) Å, c = 10.3826(6) Å), and (2-amino-5-ethylthiophen-3-yl)(2-chlorophenyl)methanone (2) crystalizes in the monoclinic P2 1 /c space group with unit cell parameters a = 10.6092(8) Å, b = 10.8355(8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
(10 reference statements)
1
13
0
Order By: Relevance
“…The structure of parent amine (VI) (see Scheme 2), namely 2-amino-3-benzoyl-4,5,6,7-tetrahydrobenzo[b]thiophene, has been reported recently (Kubicki et al, 2012) and the anisotropic displacement parameters suggest that there is disorder in the fused six-membered ring which was not accounted for in the original refinement. Accordingly, we undertook a new refinement of this structure, using the original data set, and found that there is indeed disorder in this ring, exactly comparable to the disorder found in compounds (I)-(III), with the two conformations having occupancies of 0.887 (9) and 0.113 (9) ( Fig.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…The structure of parent amine (VI) (see Scheme 2), namely 2-amino-3-benzoyl-4,5,6,7-tetrahydrobenzo[b]thiophene, has been reported recently (Kubicki et al, 2012) and the anisotropic displacement parameters suggest that there is disorder in the fused six-membered ring which was not accounted for in the original refinement. Accordingly, we undertook a new refinement of this structure, using the original data set, and found that there is indeed disorder in this ring, exactly comparable to the disorder found in compounds (I)-(III), with the two conformations having occupancies of 0.887 (9) and 0.113 (9) ( Fig.…”
Section: Figurementioning
confidence: 99%
“…It is somewhat disappointing to note that structures with unmodelled disorder, such as compound (VI) (Kubicki et al, 2012), are still being published and thus incorporated into the Cambridge Structural Database (Groom et al, 2016). In this connection, we have recently noted (Rajam et al, 2017) an example of unmodelled conformational disorder involving a simple thiophene group (Rajam et al, 2015).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations